Cleidocranial dysplasia associated with dentigerous cyst—review of literature and case report of two siblings - Nandini Bhardwaj; Abhiney Puri; Vijay Wadhwan; Monika Gupta (Indian Journal of Pathology and Microbiology)
Cleidocranial dysplasia (CCD) is a developmental anomaly of the skeleton and teeth which may be inherited, be transmitted as dominant characteristics in either male or female or even appear spontaneously. A case was reported in the department of oral medicine and radiology of two sisters age 17 and 19 years old with a chief complaint of milk teeth not falling since childhood. They presented specific physical and oral findings in common which suggested the idea of an undiagnosed syndrome. The sisters showed CCD characteristics including short stature (4 feet) and frontal bone resorption indicating delayed closure of fontanels. The stature is moderately shortened with the neck appearing long and narrow and the shoulders markedly dropped. Dental abnormalities such as retention of primary dentition, multiple supernumerary teeth, and delayed eruption of permanent dentition. OPG showed the presence of multiple impacted permanent and supernumerary teeth with radiolucency involving the crowns of impacted teeth revealing a cystic lesion. Lateral cephalogram also revealed the presence of multiple impacted teeth. The provisional diagnosis of CCD with dentigerous cyst was given. The enucleation of cyst was done and submitted for histopathological examination. Histopathologically, the soft tissue section suggested the features of dentigerous cyst. The final diagnosis of CCD associated with dentigerous cyst was confirmed.